(untitled) (Research, Society and Development, 2021)
The tension type headache (CTT) is a pain present in the daily life of many citizens, it is of multifactorial origin and is closely linked to intrinsic factors such as the emotional and extrinsic as the environment. This study is a bibliographic review of narrative character and analytical approach, between the period 2015 to 2020, sought to prove through scientific foundations the benefits that manual therapy techniques bring to patients with this algia, Identifying your treatment only by using drugs. The current research was based on articles from the sources of Google Scholar, Scielo, Pubmed, Pedro and Jospt databases. The inclusion criteria were articles that presented a direct relationship with the proposed theme, studies that addressed the manual therapies used and concluded with positive results. Articles that did not meet the above inclusion criteria and that did not indicate positive aspects of headache with manual therapies were excluded. From the application of the criteria, 12 articles were selected in accordance with the theme of the study. After the analysis and discussion of the data, it was evidenced through the results the positive effects that the manual therapeutic methods bring to headache, the main techniques were addressed in this study that totaled 13 manual therapies. The research showed that the benefits promote not only the improvement in CTT, but also brought beneficial results in improving the quality of life, functionality and quality of sleep.